Tantum bonam clausulam inpone: suicide, writing, and (self)exemplarity in Sen., Ep.77 (Circe de clásicos y modernos, 2018)
Assuming that in his Epistulae Seneca actively appropriates the discourse of exemplarity, we intend to analyze the connections between suicide, writing, and (self)exemplarity in Ep. 77. Our hypothesis is that, through writing this letter, the epistolary ego tries to direct the reader’s attention towards his ideal of an exemplary death, with the aim that this model lasts in the audience’s memory, and thus casts his own exemplarity into the future.
Keywords: Seneca; Epistulae; suicide; writing; (self)exemplarity